A Chance-Constrained Approach to Urban Renewal Decisions - Mao, James C. T.; Wright, Roger L. (Journal of Financial and Quantitative Analysis, 1968)
If all urban renewal projects were perfectly divisible and completely independent of one another, and if the urban renewal authority had perfect foresight as well as unlimited funds, the investment decision would be ideally simplified. There would be no need to choose between competing projects, and the urban renewal authority could evaluate each project on its own merits, without reference to any other project. Its decisions would be merely decisions to accept or reject single projects, uncomplicated by portfolio considerations.